Differences in the Ratios of General and Dental Specialists in Europe - Javier Fernández-Serrano; Eugenia García-Espona; José Antonio Alarcón; Cristina García-Espona; Ignacio García-Espona (Elsevier, 2024)
ABSTRACT: Background: The European Economic Area (EEA) is composed of member states with a multitude of different regions. This study aimed to analyse the ratios of general dentists and dental specialists to the total population and the proportion of dental specialists to general dentists in 24 European countries and to explore specific intranational differences within 2 countries: France and Germany. Methods: Available official documents and webpages from the United Kingdom and 23 of the 30 countries comprising the EEA were analysed. Data were expressed as absolute values, ratios of general dentists and dental specialists in the total of population, and percentages of dental specialists/dentists. The Mann-Whitney U test was used to clarify the main ratios that distinguish France from Germany, and cluster analysis was employed to determine similar areas. Results: Significant differences were found between countries, with Ireland and Austria having the lowest ratio of dentists and Romania and Greece having the highest. The Czech Republic, the Netherlands, France, and Denmark had the lowest ratios of dental specialists to the total population. Lithuania, Sweden, and Germany had the highest number of dental specialists. Orthodontists were the most numerous specialists (5.0% of dentists), followed by oral surgeons (2.7%). In France, differences between departments were pronounced and associated with the presence of dental schools and per capita income. In Germany, only the correlation between per capita income and the density of oral surgeons was significant. Conclusions: Diverse ratios of general dentists and dental specialists to the total population and the proportion of dental specialists to general dentists were discovered within the examined countries, and their maximum values were 2.5, 5.7, and 4.1 times the minimum values, respectively. Differences were even found within the same country, as was the case in France and, to a lesser extent, in Germany.